2021
DOI: 10.3390/ijerph18084059
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness in Volleyball Athletes Following a COVID-19 Infection: A Cross-Sectional Study

Abstract: Athletes’ lifestyles have been dramatically affected by the coronavirus disease 2019 (COVID-19) pandemic. Since COVID-19 primarily affects the respiratory system and to a lesser degree the cardiovascular system, the goal of this study was to examine the effects of COVID-19-caused detraining on cardiorespiratory fitness (CRF) of recently recovered volleyball athletes. Sixteen experienced volleyball athletes (age 24 ± 4.5 years) who were recently diagnosed and recovered from a COVID-19 infection volunteered to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 32 publications
(40 reference statements)
3
40
2
1
Order By: Relevance
“…In this context, Milovancev et al evaluated professional volleyball players three weeks after convalescence of COVID-19. While this cohort is thought to be well trained before SARS-CoV-2 infection, peak V̇O 2 /kg was deteriorated likewise in CPET [ 60 ], allowing for a concept of EC limitation pathogenesis after COVID-19 beyond pre-existing mitochondrial density and physical training.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Milovancev et al evaluated professional volleyball players three weeks after convalescence of COVID-19. While this cohort is thought to be well trained before SARS-CoV-2 infection, peak V̇O 2 /kg was deteriorated likewise in CPET [ 60 ], allowing for a concept of EC limitation pathogenesis after COVID-19 beyond pre-existing mitochondrial density and physical training.…”
Section: Discussionmentioning
confidence: 99%
“…They were unable to estimate the effect of detraining on their performance, as they had had no baseline examination before COVID-19 infection. They also did not have a non-COVID control group at the same training status [ 34 ]. A study investigated the effect of an eight-week lockdown period on ten elite male handball players.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the impact of COVID-19 infection on the cardiorespiratory systems of athletes [ 15 , 16 ]. One such study was conducted on female volleyball players and found that pulmonary function after COVID infection was above 80% of the predicted values for each of the participants, although electrocardiography did not find signs of ischemia, arrythmias, or conduction or repolarization abnormalities [ 16 ]. The authors concluded that the studied athletes experienced the typical consequences of missing training for a period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of information about the influence of COVID-19 infection on an athlete’s physical capacities, very few studies have looked at the impact of COVID-19 infection on the working capacities of athletes [ 15 , 16 ]. Additionally, to the best of our knowledge, no study has thus far examined the influence of COVID-19 infection on the performance of athletes in real sport settings.…”
Section: Introductionmentioning
confidence: 99%